Linguagem e cultura: recontextualização da renda de bilro catarinense na moda brasileira - Clasen, Mary Neuza de Freitas (2013)
The following work has the objective of searching for the continuity of the practice and production of the bobbin lace in Santa Catarina state, setting out its insertion into the fashion full scope once these two semiotic fields, due to their differences, are rarely correlated. In order to do that, we collected information about acts and projects which promote the practice and production of the bobbin lace; verify the possible ways and the necessary procedures for the insertion of this product into the fashion scope; develop an alternative source of consulting that can become a reference for fashion researchers and professionals that wish to acknowledge this artwork and apply it to their projects. This research also presents a necessary recontextualization of the bobbin lace for the purpose of renewing its tradition, and promote the endurance and identity of this handicraft activity which is being menace to disappear as a cultural manifestation of the coastal area of Santa Catarina state. Based on the bibliographic and field research, we organized a brief history line about the bobbin lace, described its production process and point out a possible solution to make this artwork come to life again, in fashion.